Modular Construction: A Comprehensive Review - Mohammadamin Zohourian; Apurva Pamidimukkala; Sharareh Kermanshachi; Deema Almaskati (Buildings)
Modular construction has the potential to transform the construction industry, as most (80–95%) of the modules, which are considered prefabricated buildings, are manufactured off-site, which is more efficient, safe, cost-effective, sustainable, productive, and faster than traditional construction. It is not without challenges, however, as it requires detailed and comprehensive planning, high initial costs, and navigating transportation and design constraints. The goal of this study was to identify and categorize the benefits and challenges of modular construction and offer strategies for resolving the challenges. This study also provides a comprehensive review of modular construction methods, including permanent modular construction (PMC), movable modular construction (RMC), volumetric modular construction (VMC), and panelized construction, and examines the connectivity of the modules, as well as the integration of advanced technologies like artificial intelligence (AI). The results revealed that the most frequently cited benefits of modular construction were reducing construction time by up to 50%, 20% cost savings, and material waste reduction of up to 83%. The most common challenges included transportation complexity, limited design flexibility, and high initial costs. The results of this study will assist project managers, construction professionals, and company owners in evaluating modular construction by providing quantified benefits and challenges, a comparative analysis of different modular methods, and insights into effective mitigation strategies, allowing them to assess its suitability based on project timelines, budgets, design requirements, and logistical constraints.